Numerical simulation of high-current ion beam transportation at the presence of compensating electron beams in a LIA section - Karas’, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2017)
Transportation of a high-current ion beam (HCIB) with various currents was studied in the presence of accom-panying and additional electron beams' injection in the linear induction accelerator (LIA) section. The investigations were carried out by means three-dimensional numerical simulation within the framework of the complete Vlasov-Maxwell system of equations. The parameters of the system and beams have been optimized in so way, that the ion beam quality remains acceptable for a number of important technological applications at the exit of the LIA section.